Transfusion transmissible infections in blood donors presenting at department of hematology, Jinnah Hospital, Lahore - Ahmad, Rabia; Ch, Sidra Sonia; Rehan, Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of transfusion transmissible infections in blood donors presenting at department of hematology, Jinnah Hospital, Lahore. Material and methods: This cross sectional study was conducted at Department of Hematology, Jinnah Hospital, Lahore from March 2021 to September 2021. Total 190 blood donors presenting at Blood Bank having age 17-65 years both male and female were recruited. Transfusion transmissible infections in blood donors were studied. Results: Age range in this study was from 17 to 65 years with mean age of 39.59 ± 9.04 years. Majority of the blood donors 124 (65.26%) were between 17 to 40 years of age. Out of the 190 blood donors, 140 (73.68%) were male and 50 (26.32%) were females with male to female ratio of 2.8:1. In this study, I have found the hepatitis B in 08 (4.21%), hepatitis C in 17 (8.95%), HIV in 01 (0.53%) and syphilis in 04 (2.11%) blood donors. Conclusion: This study concluded that prevalence of HCV, HBV, HIV and Syphilis in blood donors was 8.95%, 4.21%, 0.53% and 2.11% respectively.